Factors influencing training requirements in hospitals: an integrative literature perspectives: RECTRACTED: This article has been retracted by editorial decision, as it was determined that its content does not fit the thematic scope of the journal. The retraction is not due to any ethical misconduct on the part of the authors. - AlFlayyeh, Saad; Rahman Al-Homeed, Abdullah Abdul (Nexo Revista Científica, 2023)
Training is not a new phenomenon and trend, but it requires continuous efforts and developments due to the dynamic change in our society. Gaps will remain if training and development programs not developed timely. Present study is the combination of Gulf and other world studies about the training and development programs to highlight the importance of training and development programs, and why it is so necessary. Contemporary study then suggests the conceptual study framework and assumed the hypotheses. In the conceptual framework, it is basically shown that there is influence of training and development programs. Some influence internally, whereas some impacts are externally. And finally it has impact on the overall organization performance.